Bringing together podcasting, social work field education and learning about practice with Aboriginal peoples and communities. - Fox, Mim; McHugh, Siobhán; Thomas, Denika; Kiefel-Johnson, Felix; Joseph, Ben (Social Work Education, 2023)
Social work content podcasting has increased exponentially in recent years, playing a new role in the emerging social work education debate surrounding online and remote delivery of social work content. Although podcasting itself is not now a new digital innovation, how and why social work educators and academics would embrace the use of podcasting is still debated and is often positioned as inferior to face-to-face classroom teaching. In the Australian context this is particularly important when non-Aboriginal students are engaging with Aboriginal understandings of place and ways of relating to Country, a challenging reflexive exercise without the added complexity that remote educational delivery can provide. The brief history of podcasting and its relationship to social work education provides a context for re-imagining the pedagogy of critical thinking, with a case example provided of a remote field placement with The Social Work Stories Podcast during the Covid-19 pandemic in 2020.